La incidencia de la evolución de los aprendizajes en el rendimiento académico de los estudiantes de básica media de la escuela de Educación Básica "Inés Gangotena Jijón" de la ciudad de Sangolquí, cantón Rumiñahui, provincia de Pichincha en el año lectivo 2015-2016 y con la propuesta del diseño de un manual de estrategias metodológicas de evaluación de los aprendizajes. - Villamarín Villamarín, Marizol Dolores (2016)
This research is based on the assessment of learning and its impact on the academic performance of Medium Basic students from "Inés Gangotena Jijón" School in which a field investigation was carried out, allowing observe underachievement, as evidence that learning assessment models are not being optimized with innovative assessment instruments according to the conceptual paradigm. The investigation determined that the relationship between the variables, evaluation and performance are decisive in the teaching-learning process, therefore this process should be active, considering the styles and rhythms of students learning; learning as a mental process is the acquisition of relevant information that involves the participation of mindsets, such as perception, attention, memory and critical thinking that once assimilated by the student allows them to perform complex mental operations to analyze, interpret, synthesize, compare, etc., and finally generate learning, which should be evaluated with appropriate evaluation instruments that generate trust and confidence in students, parents and teachers. This information should not only be used to obtain a quantitative but a qualitative assessment rating that will enable learning feedback that were not properly assimilated by the student. This research process was performed to the focus groups of the entire educational community, through surveys to students, parents and mothers, teachers and an interview to the district administrator, obtaining reliable information in the same place where the investigated events happen, which allowed to elaborate conclusions and recommendations, validating the "Manual of Methodological Strategies assessment of Learning" proposal that will provide guidance and support for teachers of Inés Gangotena Jijón School, improving evaluation processes and achieving an integral training of students.